Estratégia autônoma para conectividade e comunicação em ambientes inteligentes - Vieira, Ildo Ramos (2016)
The future of the Internet trend is a new form of communication that will expand the current human-human model to reach the human-object communication and object-object, where each object can be identified and connected to the Internet, once he has the proper technology. This new scenery will lead to communication between humans to be a minority in relation to objects. These objects will be able to exchange large amounts of information with each other, and, in most cases, the only responsible for generating and receiving traffic, with little or no supervision. In this new scenery, the use of mobile devices is transforming the way users interact, allowing applications to explore the physical proximity of others to offer intelligent services. These devices are increasingly powerful computationally and diversified in terms of communication interfaces. This diversity increases the connectivity of devices to their environment, but makes choosing the best connection more complex and dependent on context. In this sense, we have developed an autonomous strategy for connection and communication in intelligent environments able to offer developers application new features that can help to reduce the complexity of the interactions between devices using mechanism for intelligent connectivity in order to facilitate communication between the Internet devices of Things, where the decision is based on criteria defined by the metrics of the network and context. Experimental results show that the behavior of a system that utilizes the features developed in fact adapt to environmental variations connectivity.